The effect of dynamic lactic training according to the target time fo developing special endurance, lactic acid concentration, and achievement for 800m runners under20 years old - Mahdi, Marwa; kadhim, Hamedd (Journal of Physical Education, 2023)
Athletics is one of the most important individual games in the world, which is widely practiced and includes many activities, including short-distance and long-distance running and marathons, as well as throwing events and jumping and jumping activities, which need educational and training curricula in order to develop these events. Therefore, the importance of the research lies in preparing dynamic lactic exercises according to the target time to develop endurance for 800m runners (under 20 years old) in order to raise the physical and physiological levels that raise the readiness of the runners to achieve what they want. The research sample represents the activity of running (800 m) under 20 years old, whose number is (6) runners who represent 100% of the community of origin from the elite of Baghdad. For special endurance using dynamic lactic exercises.The statistical bag (spss) was used to extract the results.By presenting, analyzing and discussing the results, it was found that there is an effect of dynamic lactic exercises according to the time spent in developing the special endurance of 800m (under 20 years old) between the two groups and in favor of the experimental group. Summary of the research